2020
DOI: 10.18632/aging.102955
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits high glucose-induced smooth muscle cell proliferation and migration

Abstract: We investigated the protective effects and mechanism of action of metformin on high glucose-induced smooth muscle cell proliferation and migration. Vascular smooth muscle cells (VSMCs) were subjected to a series of concentrations (0-10 mM) of metformin. CCK-8, wound healing, and transwell assays were performed. Correlations between metformin concentration and high-mobility group box 1 (HMGB1) and miR-142-3p levels were assessed. In addition, miR-142-3p mimic and siRNA were used to investigate VSMC migration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
(52 reference statements)
2
28
2
2
Order By: Relevance
“…Notably, in vitro studies attempted to determine whether HG led to inhibition or activation of autophagy. HG resulted in decreased LC3II levels and elevated p62 levels in vascular smooth muscle cells 24 ; similarly, inhibition of HG-mediated autophagy was observed in the human neuroblastoma cell lines 25 . By contrast, Zhao et al established that excessive autophagy in H9c2 cells was induced in a HG medium 26 .…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Notably, in vitro studies attempted to determine whether HG led to inhibition or activation of autophagy. HG resulted in decreased LC3II levels and elevated p62 levels in vascular smooth muscle cells 24 ; similarly, inhibition of HG-mediated autophagy was observed in the human neuroblastoma cell lines 25 . By contrast, Zhao et al established that excessive autophagy in H9c2 cells was induced in a HG medium 26 .…”
Section: Introductionmentioning
confidence: 71%
“…In OA, a converse outcome of defective autophagy was observed in diabetic patients with OA and experimental mice, suggesting that HG could compromise autophagy capacity in diabetic patients with OA 22 , 23 . The studies revealed contrasting results for in vivo experiments because the effects of DB on autophagy rather than HG could be attributed to several factors such as aging, inflammation, vascular injury, etc 24 , 25 . Notably, in vitro studies attempted to determine whether HG led to inhibition or activation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found that metformin signi cantly reduced the migration ability of VSMCs induced by HG but had no signi cant effect on the proliferation of VSMCs. Dong M Zhou et al [37] also found similar results using metformin that inhibited HG-induced VSMC proliferation and migration by promoting the mir-142-3p mediated HMGB1 expression. The mechanism of metformin-mediated inhibition of migration still needs to be further studied.…”
Section: Discussionmentioning
confidence: 64%
“…For example, telmisartan and irbesartan promote autophagy through the proliferator activated receptor-γ (PPARγ) and telmisartan attenuates lipid accumulation in VMSCs, which is rescued by Atg7 knockdown [ 191 , 192 ]. Finally, the widely used anti-diabetic drug metformin is an established inducer of endothelial cells and VSMCs autophagy and exerts anti-atherosclerotic features [ 193 , 194 , 195 , 196 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%